ITO‐free top emitting organic light emitting diodes with enhanced light out‐coupling. Issue 1 (6th November 2013) - Yambem, Soniya D.; Ullah, Mujeeb; Tandy, Kristen; Burn, Paul L.; Namdas, Ebinazar B.
<x xml:space="preserve">Abstract</x> Bottom emitting organic light emitting diodes (OLEDs) can suffer from lower external quantum efficiencies (EQE) due to inefficient out‐coupling of the generated light. Herein, it is demonstrated that the current efficiency and EQE of red, yellow, and blue fluorescent single layer polymer OLEDs is significantly enhanced when a MoOx(5 nm)/Ag(10 nm)/MoOx(40 nm) stack is used as the transparent anode in a top emitting OLED structure. A maximum current efficiency and EQE of 21.2 cd/A and 6.7%, respectively, was achieved for a yellow OLED, while a blue OLED achieved a maximum of 16.5 cd/A and 10.1%, respectively. The increase in light out‐coupling from the top‐emitting OLEDs led to increase in efficiency by a factor of up to 2.2 relative to the optimised bottom emitting devices, which is the best out‐coupling reported using solution processed polymers in a simple architecture and a significant step forward for their use in large area lighting and displays. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>